Familial risk of non-Hodgkin lymphoma by sex, relationship, age at diagnosis and histology: a joint study from five Nordic countries - Fallah, Mahdi; Kharazmi, E.; Pukkala, E.; Tretli, S.; Olsen, J. H.; Tryggvadottir, L.; Sundquist, K.; Hemminki, Kari (Leukemia, 2016)
We aimed to estimate stratified absolute (cumulative) and relative (standardized incidence ratios; SIRs) risks of non-Hodgkin lymphoma (NHL) in relatives of NHL patients. A cohort of 169 830 first-degree relatives of 45 406 NHL patients who were diagnosed between 1955 and 2010 in five European countries was followed for cancer incidence. The lifetime (0-79 year) cumulative risk of NHL in siblings of a patient with NHL was 1.6%, which represents a 1.6-fold increased risk (SIR=1.6, 95% confidence interval (CI)=1.2-1.9) over the general population risk. NHL risk among parent−offspring pairs was increased up to 1.4-fold (95% CI=1.3-1.5; lifetime risk 1.4%). The lifetime risk was higher when NHL was diagnosed in a sister (2.5% in her brothers and 1.9% in her sisters) or a father (1.7% in his son). When there were ⩾2 NHL patients diagnosed in a family, the lifetime NHL risk for relatives was 2.1%. Depending on sex and age at diagnosis, twins had a 3.1-12.9% lifetime risk of NHL. Family history of most of the histological subtypes of NHL increased the risk of concordant and some discordant subtypes. Familial risk did not significantly change by age at diagnosis of NHL in relatives. Familial risk of NHL was not limited to early onset cases.